PERBAIKAN SISTEM PENDINGIN DAN PENGEREMAN PADA MESIN BUBUT DO ALL BERBASIS KOREKTIF MAINTENANCE DI BENGKEL POLMAN BABEL - Syukori Putra, Nurul; Irwansyah, Riko; Tuparjono, Tuparjono; Rodika, Rodika (Politeknik Manufaktur Negeri Bangka Belitung, 2025)
This study aims to repair the cooling and braking systems of the DoAll LT 13 lathe at the Polman Babel Workshop by applying the Corrective Maintenance method. This lathe has been in operation for 28 years and has experienced failures in both the cooling and braking systems, resulting in decreased performance. The repair process began with problem identification using the 5 Why method to find the root causes of the failures. The analysis revealed that the main issues were a non-functional electric motor and the absence of caliper and master cylinder components. The repair steps included replacing the electric motor, installing the cooling hose and valve, and modifying the braking system using spare parts from a Panther vehicle. Testing after the repairs showed that both the cooling and braking systems were functioning properly. This study concludes that the application of Corrective Maintenance is effective in restoring the functionality of the DoAll LT 13 lathe and ensuring the availability of the machine for student practical activities.